APLIKASI SISTEM PENGAJUAN DAN PENGELOLAAN DATA KARYAWAN BANK BNI DIVISI CLN BERBASIS WEB - Muhammad Fikri Aqsal Pratinko (2022)
In the activities of managing employee data at BNI, the CLN division still uses the manual method. This manual method of managing employee data is not efficient because it takes a lot of time in the process of delivering the information. The role of the system in helping employee performance is to produce relevant and precise information on the existing data. An information system is data that is processed into a form that is useful for its users. Processed data alone is not enough to be said as an information. To be useful, information must be supported by three pillars as follows: Employee data management applications are made using HTML and PHP, MySQL as database server, and designed using prototyping methods. The results of this study are employee and information management applications that have been able to manage employee data, submit job promotions, incoming and outgoing letters.